Tanaman Obat Keluarga (TOGA) sebagai Minuman Herbal Peningkat Daya Imun Tubuh - Ernie Halimatushadyah; Agnes Yuliana (Yayasan Inspirasi El Burhani, 2023)
Introduction: Transmission of infectious diseases cannot be separated from the interaction between the causative agent of the disease host and the environment. Efforts to increase the host's immune system to survive infectious attacks are also important things to do, including the use of Family Medicinal Plants (TOGA). Family Medicinal Plants (TOGA) are nutritious plants planted in the house’s yard and managed by the family Objective: The problem faced today is the availability of herbal plants in the yard that has not been utilized. Method: This community service was carried out with residents of RW 07 Cawang, with 28 people participating in the activity. Community service is carried out using presentation methods, providing information through flayers, workshops for making herbal drinks, and question-and-answer discussions. Result: The questionnaire results showed that 28 participants (100%) had ever drunk traditional drinks but 11 participants (39.30%) did not know how to make traditional products. Conclusion: The results obtained are that the service participants have the ability of herbal plants to become beverage products that can increase endurance.